Texturing & modeling a procedural approach - Ebert, David S., 1964- (San Francisco, Calif. : Morgan Kaufmann, 2003)
The third edition of this classic tutorial and reference on procedural texturing and modeling is thoroughly updated to meet the needs of today's 3D graphics professionals and students. New for this edition are chapters devoted to real-time issues, cellular texturing, geometric instancing, hardware acceleration, futuristic environments, and virtual universes. In addition, the familiar authoritative chapters on which readers have come to rely contain all-new material covering L-systems, particle systems, scene graphs, spot geometry, bump mapping, cloud modeling, and noise improvements. There are many new spectacular color images to enjoy, especially in this edition's full-color format. As in the previous editions, the authors, who are the creators of the methods they discuss, provide extensive, practical explanations of widely accepted techniques as well as insights into designing new ones. New to the third edition are chapters by two well-known contributors: Bill Mark of NVIDIA and John Hart of the University of Illinois at Urbana-Champaign on state-of-the-art topics not covered in former editions. An accompanying Web site (www.texturingandmodeling.com) contains all of the book's sample code in C code segments (all updated to the ANSI C Standard) or in RenderMan shading language, plus files of many magnificent full-color illustrations. No other book on the market contains the breadth of theoretical and practical information necessary for applying procedural methods. More than ever, Texturing & Modeling remains the chosen resource for professionals and advanced students in computer graphics and animation. *New chapters on: procedural real-time shading by Bill Mark, procedural geometric instancing and real-time solid texturing by John Hart, hardware acceleration strategies by David Ebert, cellular texturing by Steven Worley, and procedural planets and virtual universes by Ken Musgrave. *New material on Perlin Noise by Ken Perlin. *Printed in full color throughout. *Companion Web site contains revised sample code and dozens of images.
Introduction; Building Procedural Textures; Real-Time Programmable Shading by William R. Mark; Cellular Texturing; Advanced Antialiasing; Practical Methods for Texture Design; Procedural Modeling of Gases; Animating Solid Spaces; Volumetric Cloud Modeling with Implicit Functions; Issues and Strategies for Hardware Acceleration of Procedural Techniques; Procedural Synthesis of Geometry by John C. Hart; Noise, Hypertexture, Antialiasing, and Gesture; Real-Time Procedural Solid Texturing by John C. Hart; A Brief Introduction to Fractals; Fractal Solid Textures: Some Examples; Procedural Fractal Terrains; QAEB Rendering for Procedural Models; Atmospheric Models; Genetic Textures; MojoWorld: Building Procedural Planets; On the Future: Engineering the Appearance of Cyberspace.
Includes bibliographical references (p. 629-652) and index.
Keywords: Computer programming; Computer graphics; Electronic books